Three-year analysis of the Belgian multidisciplinary immunotoxicity (BITOX) board: organization, feasibility, and results - M. Verhaert; Y. Aydogan; S. Aspeslagh (ESMO Real World Data and Digital Oncology)
Background: With the increasing use of immune checkpoint inhibitors (ICIs), immune-related adverse events (irAEs) have become more prevalent in oncological practice. Clinical approaches vary due to the exclusion of patients with comorbidities from trials and the lack of long-term data on irAEs. As irAEs can affect any organ system, sometimes becoming life-threatening, and their immunosuppressive treatments may influence oncological outcomes, collaboration between oncologists and organ specialists familiar with autoimmune syndromes is essential. The goal is to share experiences, learn, and identify clinically relevant research questions. Methods: The Belgian multidisciplinary ImmunoTOXicity board (BITOX) is a virtual meeting for oncologists and organ specialists held biweekly (every two weeks). Health care providers submit questions about irAE diagnosis, management, and ICI safety in dysimmune patients through an electronic form. Dysimmunity is defined by the presence of autoimmune disease, solid organ transplantation, ongoing antiviral or antibiotic treatment, corticosteroid therapy, paraneoplastic syndrome, Eastern Cooperative Oncology Group (ECOG) performance status >2, pregnancy, or a history of irAE. This paper presents a retrospective, descriptive analysis of the cases discussed over the past 3 years. Results: Between March 2021 and March 2024, 246 clinical cases from 131 submitting physicians were discussed. The majority (n =142) concerned irAE management. Most patients were treated with anti-programmed cell death protein 1 monotherapy (n = 111; 45.1%) and had dysimmune comorbidities (n = 162; 65.9%). Neurological (n = 35; 14.2%) and rheumatological (n = 32; 13%) irAEs were the most frequently submitted. Conclusions: The establishment of a national, virtual, multidisciplinary immunotoxicity board in Belgium is feasible and highlights relevant future research questions. It enhances multidisciplinary discussion of ICI-related issues in Belgium.